2021
DOI: 10.1186/s12935-021-02032-5
|View full text |Cite
|
Sign up to set email alerts
|

DNA double-strand break repair gene mutation and the risk of papillary thyroid microcarcinoma: a case–control study

Abstract: Objective To study the relationship between DNA double-strand break (DSB) repair gene mutations and the risk of papillary thyroid microcarcinoma (PTMC). Methods One hundred patients with PTMC or benign thyroid nodules (BTNs) at Henan Cancer Hospital were retrospectively analyzed. The DSB repair capacity of peripheral blood T lymphocytes in the two groups was assessed by flow cytometry. Data were compared using Student’s t-test to evaluate the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The biological distinctions across thyroid tumor types may be more substantial than the variances between radioiodine-resistant and radioiodine-sensitive cancers [ 18 ]. Additionally, the study by Qin et al has found that radiation exposure is linked to mutations in genes responsible for repairing double-strand breaks (DSBs), thereby reducing the ability to repair DSBs and resulting in papillary thyroid microcarcinoma (PTMC) [ 19 ]. Similarly, dysfunctions in DNA repair were demonstrated to be significant in the clonal evolution of thyroid carcinoma [ 20 ].…”
Section: Thyroid Cancer Dna Damage and Repairmentioning
confidence: 99%
“…The biological distinctions across thyroid tumor types may be more substantial than the variances between radioiodine-resistant and radioiodine-sensitive cancers [ 18 ]. Additionally, the study by Qin et al has found that radiation exposure is linked to mutations in genes responsible for repairing double-strand breaks (DSBs), thereby reducing the ability to repair DSBs and resulting in papillary thyroid microcarcinoma (PTMC) [ 19 ]. Similarly, dysfunctions in DNA repair were demonstrated to be significant in the clonal evolution of thyroid carcinoma [ 20 ].…”
Section: Thyroid Cancer Dna Damage and Repairmentioning
confidence: 99%